Gender stereotypes, self, and sport dropout: a one-year prospective study in adolescents - Plaza, M.; Boiché, J. (Movement & Sport Sciences - Science & Motricité, 2017)
Introduction. Gender stereotypes were previously shown to be associated with sport dropout, but this literature remains scare and the results observed are limited by the design used, the focus on explicit stereotypes, the absence of consideration of individuals' gender-identity, and of the gendered-nature of sports. Objective. This one-season prospective study examined gender stereotypes (explicit and implicit) and self-perceptions (gender- as well as sport-related), in relationship to dropout intentions and behavior among adolescent athletes practicing feminine, neutral or masculine sports. Method. Explicit gender sport stereotypes, self-perceptions of sport value and competence, and gender centrality were assessed by questionnaire. Gender-sport and self-gender automatic associations were evaluated with two Brief-Implicit Association Tests (B-IAT; Sriram, N., & Greenwald, A.G. (2009). The Brief Implicit Association Test. Experimental Psychology, 56, 283-294. DOI: 10.1027/1618-3169.56.4.283) Titel anhand dieser DOI in Citavi-Projekt übernehmen. Results and conclusion. Pro-masculine sport stereotypes and sport self-perceptions were higher in boys and in adolescents practicing masculine sports. Also, sport self-perceptions were positively predicted by sport stereotypes in favor of one's sex in-group, whatever the centrality of gender in adolescents' identity. Last, athletes with stronger intentions displayed higher sport self-perceptions of value and competence, and were more likely to actually pursue their activity one year later.